2022
DOI: 10.3892/ol.2022.13588
|View full text |Cite
|
Sign up to set email alerts
|

Role of tumor‑associated neutrophils in lung cancer (Review)

Abstract: Lung cancer is the most common malignancy and the leading cause of cancer mortality worldwide; therefore, it is very important to understand the mechanism of its occurrence and progression. It has reported that inflammation is linked to the incidence of various malignancies. Neutrophils not only participate in the inflammatory response, but are also involved in the composition of the tumor microenvironment. Tumor-associated neutrophils (TANs) are infiltrating neutrophils in tumors that directly promote tumor d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 119 publications
2
5
0
Order By: Relevance
“…46 These cells are associated with poor prognosis in breast cancer, 47 colorectal cancer, 48 gastric cancer, 49 and lung cancer. 50,51 Our study supported these conclusions. In addition, the HR group was found to have elevated levels of APC coinhibition and MHC-I, while the LR group had a better HLA and type II IFN immune status.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…46 These cells are associated with poor prognosis in breast cancer, 47 colorectal cancer, 48 gastric cancer, 49 and lung cancer. 50,51 Our study supported these conclusions. In addition, the HR group was found to have elevated levels of APC coinhibition and MHC-I, while the LR group had a better HLA and type II IFN immune status.…”
Section: Discussionsupporting
confidence: 87%
“…In the tumor stroma of different human cancer types, increased mast cell density is linked with either good or poor prognosis, depending on the tumor type and stage. , In most tumors, neutrophils are linked with chronic inflammation and are favorable for the growth and development of invasive phenotypes of tumors . These cells are associated with poor prognosis in breast cancer, colorectal cancer, gastric cancer, and lung cancer. , Our study supported these conclusions. In addition, the HR group was found to have elevated levels of APC coinhibition and MHC-I, while the LR group had a better HLA and type II IFN immune status.…”
Section: Discussionsupporting
confidence: 81%
“…Most studies have investigated the relationship between neutrophils and the long-term prognosis of ICIs treatment, very few studies have investigated their relationship with the short-term efficacy of ICIs has. Moreover, studies ( 46 ) have shown that neutrophils can stimulate T cell response and increase anti-tumor response in the early stage of immunotherapy. In addition, there exists a heterogeneity of neutrophils and complex responses in the tumor immune microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Chemokines secreted by both tumor cells and TME play a central role in regulating the recruitment of immune cells such as neutrophils [31]. Notably, the in ltration of tumor-promoting neutrophils leads to increased tumor progression [31] and is normally associated with high-grade aggressive tumors [32].…”
Section: Nkx2-1-low Tumors Promote Neutrophil In Ltration Via CXC Che...mentioning
confidence: 99%